Reading for gain or reading for fun: empirical evidence from China on the adoption mechanism of integrated children’s books - Cui, Jiayong; Guo, Jing; Yang, Jiaomin; Wu, Lingyu; Bao, Yinuo (Frontiers in Psychology, 2024)
With the increasing number of children publications that integrate new media technologies in the global publishing community, understanding the adoption and use of these publications from a children's perspective is of great significance for both children education practitioners and the publishing industry. This paper integrates a dual effect path based on Utilitarian Motivation System (UMS) and Hedonic Motivation System (HMS) on information technology adoption, through the questionnaire, systematically demonstrating the psychological mechanism of children's reading about integrated books. This study finds that children's willingness to use integrated children's books is related to UMS and HMS except for Facilitating Conditions. What's more, this study also reveals the structural differences existing in adoption psychology of children from various age groups and home education background. This study provides a systematic explanation for understanding the adoption psychology of integrated children's books. Based on these findings, it is suggested that publishers should balance the concept of Education-Orientation and Child-Orientation when making children's books, conduct technical innovation of children's books according to children individual, meanwhile, constantly innovate the service mode to avoid the risk of children's bad reading.